Application of Acceptance Commitment Therapy in Schizoaffective Patients with Hallucinations and Self-Care Deficits - Yanuar Fahrizal; Novy Helena Chatarina Daulima; Mustikasari Mustikasari (Jurnal Ilmu Keperawatan Jiwa, 2021)
Schizophrenia is the most widely treated psychotic disorders in mental hospitals. The prevalence of the schizoaffective disorder is difficult to determine precisely because of the limited data available. Schizoaffective disorder has positive symptoms include hallucinations and negative symptoms include self-care deficits. Interventions that can be used to resolve hallucination problems and self-care deficits, among other acceptance commitment therapy that are part of behavioral therapy. This study aims to describe cases of treatment hallucinations and self-care deficits in schizoaffective patients using acceptance commitment therapy. This study is a case report using a descriptive observational design on one patient. In this study, patients were medically diagnosed schizoaffective with nursing problems, sensory perception disorders, and self-care deficits. Patients receive treatment in the form of acceptance commitment therapy for four sessions. There was a decrease in hallucinations and self-care deficit symptoms after acceptance commitment therapy was given. Acceptance commitment therapy can reduce symptoms of sensory perception disorder hallucinations and self-care deficits in schizoaffective patient.